Pillion Simulation System (PISIS): An Exclusive System for Simulating Pillion’s Motorcycling Experience / Wan Muhammad Syahmi Wan Fauzi...[et al.] - Wan Fauzi, Wan Muhammad Syahmi; Omar, Abdul Rahman; Rashid, Helmi; Saman, AliasMohd (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In the recent years, studies in the motorcycle niche area have been an overwhelming area of research interest. Researchers utilized motorcycle simulator as an alternative assessment to conduct studies in the motorcycle niche area. However, it is noticeable that studies on motorcycle and pillion are very limited. This might be due to most of the motorcycle simulators were built exclusively for the rider, thus lack of capability to conduct experiments and assessments toward pillion. This paper deal with the development of a new simulation system for pillion motorcyclist named Pillion Simulation System (PISIS), in a controlled laboratory setting using an established motorcycle simulator, Postura MotergoTM. Integration of several elements and development of PLC programming architecture written in CX-Programmer were done. As a result, the PISIS consists of 6 compositions: i) an audiovisual element that generates the visual and environmental sound; ii) a windblast element that generates the wind from an industrial blower; iii) motion system that generates movement of the motorcycle simulator in roll axis; iv) pillion features that enable the subject to perform riding posture as pillion; v) a vibration element that generates vibration from the sound system; and vi) programming architecture that simulates the dynamic of the PISIS system. Having such system integrated into the Postura MotergoTM provides a new, safer medium and workstation for researchers to conduct continuous studies in the motorcycle niche area involving the pillion motorcyclist and hope to expand in the coming years.